2005
DOI: 10.1021/ja043373z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Circular Dichroism of Tetraarylporphyrin−Oligonucleotide Conjugates

Abstract: The preparation and circular dichroic (CD) studies of self-complimentary 8-mer DNA sequences with a porphyrin at the 3' end are presented. Electronic interaction between the two porphyrins (the interchromophoric distance is in the range of 28-40 A), attached to both ends of the double-stranded helix, gives rise to a long-range exciton-coupled CD in the visible region (400-450 nm). The porphyrin chromophores act as sensitive probes of geometrical changes in the DNA backbone and sensitively reflect the double-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
51
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 21 publications
2
51
0
Order By: Relevance
“…This negative CD exciton couplet (À/+ pattern) indicates the anticlockwise orientation of the transition dipoles of the porphyrins (Figure 4). [8,13,14] The flipping be- haviour was confirmed by the different CD profiles in the region of the Soret band for duplexes 11 and 12. Molecular modelling shows that in the nonflipped structures there is a clockwise orientation of the porphyrins' transition dipoles, which should provide a positive CD exciton couplet (+/À pattern).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…This negative CD exciton couplet (À/+ pattern) indicates the anticlockwise orientation of the transition dipoles of the porphyrins (Figure 4). [8,13,14] The flipping be- haviour was confirmed by the different CD profiles in the region of the Soret band for duplexes 11 and 12. Molecular modelling shows that in the nonflipped structures there is a clockwise orientation of the porphyrins' transition dipoles, which should provide a positive CD exciton couplet (+/À pattern).…”
mentioning
confidence: 79%
“…[4] Covalent attachment of porphyrin moieties to DNA has been achieved by using a variety of methodologies, including: the modification of nucleobases, [5][6][7][8] ribofuranose residues, [9][10][11][12][13] phosphate backbone [14][15][16] and by using acyclic linkers. [17,18] This provides structures that have porphyrin residues as 3'-or 5'-molecular caps, [12,[18][19][20] thus introducing them instead of a nucleobase in the middle of the helix [17] or as a label in the minor [10,16] and major [6][7][8] grooves.…”
mentioning
confidence: 99%
“…with positive and negative bands of the same magnitude, are characteristic of the dipole-dipole through-space electronic interaction. 9,14,40 This bisignate pattern changed its sign in comparison with the signal for the 10/1 molar ratio. This change of the spectral pattern may indicate that the conformational change from right-handed to left-handed occurred.…”
mentioning
confidence: 91%
“…9 Both UV and Soret regions were used in the ECD studies of bound porphyrin-oligonucleotide conjugates. [10][11][12][13][14] It has been shown that the CD signal of the porphyrin part of the conjugate can serve as a probe of the oligonucleotide conformation and its variation, e.g. the B-Z transitions.…”
Section: Introductionmentioning
confidence: 99%
“…They have been covalently linked to specific chiral sequences, and their CD spectral properties have been used to resolve complicated stereochemical issues [12][13][14][15] as well as monitor polynucleotide dynamics. [16] Also, the noncovalent interactions of cationic or anionic water-soluble achiral porphyrins with chiral templates have been exploited to build supramolecular species to detect and/ or amplify the handedness of the matrix. [17,18] Achiral cationic porphyrins are indeed good candidates as noncovalent probes for right-and left-handed DNA.…”
mentioning
confidence: 99%